Identification of the comparison of the length of the index finger and the ring finger - Fauzi, Agusta; Rifani Fachry (Genetikawan Muda Indonesia, 2024)
The length of the index finger (also known as the second finger or 2D finger) and ring finger (also known as the third finger or 4D finger) can be used as identifiable characteristics in humans. The relationship between the ratio of index finger length to ring finger length (2D:4D) is influenced by the hormones testosterone (in men) and estrogen (in women). Where this hormone is a hormone inherited from genes and its expression is influenced by the sex influence gene, so that there is a difference between the length of the index finger and the length of the ring finger. Estrogen and testosterone hormones that will affect the work of HOXD and HOXA in determining the length of a person's fingers. The purpose of the study was to determine the incidence of long index fingers compared to ring fingers in students and female students at SMA Muhammadiyah 1 Padang. This study shows that the difference in length between the index finger and ring finger can vary between individuals. Some studies have also found a correlation between the length of the index and ring fingers with factors such as height and genetic characteristics.